Exploring drought tolerance in wild and traditional olive varieties from the Southern Levant - Adi, Basappa; Dag, Arnon; Ben-Dor, Elad; Gabay, Gilad; Barazani, Oz (Frontiers in Plant Science, 2025)
Local olive germplasm of the southern Levant includes wild populations of var. sylvestris and local traditional cultivars that are thought to be well-adapted to the region’s arid conditions. By controlling water availability, we tested the response of the Barnea cultivar, two local traditional cultivars (MLL1 and MLL7) and var. sylvestris to low (100%), moderate (33%), and severe (10%) evapotranspiration (ETa) conditions. Measurements of stomatal conductance, relative water content, stem water potential, and the net photosynthesis showed a stronger response of the Barnea cultivar to reduced ETa conditions in comparison to the other three investigated groups. Additionally, when exposed to 100% ETa, the net photosynthesis capacity of MLL1 was significantly higher than that measured in MLL7. Therefore, net photosynthesis, as an indicator of tree productivity, can explain the dominance of MLL1 (Souri cultivar) in local traditional orchards and the negligible abundance of MLL7 (unknown cultivar) as a fruit-bearing tree. Considering that climate change is already influencing olive cultivation, the results of this study stress the potential of the southern Levant local olive germplasm in maintaining sustainable olive horticulture.